Publication manual of the American Psychological Association. (American Psychological Association, 2020)
"The Publication Manual of the American Psychological Association, Seventh Edition is the official source for APA Style. With millions of copies sold worldwide in multiple languages, it is the style manual of choice for writers, researchers, editors, students, and educators in the social and behavioral sciences, natural sciences, nursing, communications, education, business, engineering, and other fields. Known for its authoritative, easy-to-use reference and citation system, the Publication Manual also offers guidance on choosing the headings, tables, figures, language, and tone that will result in powerful, concise, and elegant scholarly communication. It guides users through the scholarly writing process-from the ethics of authorship to reporting research through publication. The seventh edition is an indispensable resource for students and professionals to achieve excellence inwriting and make a impact with their work."